Climate-smart agriculture investment plan for Ethiopia - Tesfaye, Lidya; Alemayehu, Sintayehu; Jalango, Dorcas; Karanja, Stanley; Magambo, George; Ghosh, Aniruddha; Vyas, Shalika; Nowak, Andreea C.; Wamicwe, Peter; Newman, Richard; Grosjean, Godefroy; Cosgrove, Bethany; et al. (2024)
Agriculture is the backbone of the Ethiopian economy, accounting for about 32.4% of GDP, employing over 80% of the population, and foreign currency earning. However, the sector is heavily dependent on rain-fed smallholder farming, making it highly vulnerable to climate change-induced weather extremes such as drought and flood. Studies indicate that climate change induced hazards reduce an estimated 4% of the GDP, which is projected to reduce even further reaching approximately 10% of the GDP by 2050. From this, it is clear that climate change is and remains to be a major threat to the agriculture sector and food systems in Ethiopia. This is further aggravated by land degradation and hinders the country's economic development. Thus, climate-smart agriculture (CSA) that builds sustainable agricultural production and food systems becomes crucially important for Ethiopia. The CSA strategy for the agricultural management encompasses three foundational pillars: building resilience, sustainably boosting agricultural productivity, and enhancing adaptive capacity to climate change while at the same time reducing greenhouse gas emissions to mitigate climate change wherever possible.